2004
DOI: 10.1158/1055-9965.epi-082-3
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia-Telangiectasia-Mutated ( ATM ) Gene in Head and Neck Squamous Cell Carcinoma

Abstract: The Ataxia-telangiectasia-mutated (ATM) gene product is a well-characterized tumor suppressor that plays a key role in maintenance of genomic stability. We have recently documented that the ATM promoter is a target for epigenetic silencing in cultured tumor cells. Here we show that aberrant methylation of the ATM promoter occurs in a significant percentage (25%) of head and neck squamous cell carcinomas. The presence of methylated ATM promoter shows a statistically significant correlation with an earlier age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 16 publications
4
72
1
Order By: Relevance
“…More recently, we determined that aberrant methylation of the ATM promoter occurs in a subset of head and neck tumors (Ai et al, 2004). Further, several reports showed that reduced ATM expression, as judged by immunohistochemical staining, occurs in a significant portion of breast tumors (Kairouz et al, 1999;Angele et al, 2000).…”
Section: Published Online 1 November 2004mentioning
confidence: 96%
“…More recently, we determined that aberrant methylation of the ATM promoter occurs in a subset of head and neck tumors (Ai et al, 2004). Further, several reports showed that reduced ATM expression, as judged by immunohistochemical staining, occurs in a significant portion of breast tumors (Kairouz et al, 1999;Angele et al, 2000).…”
Section: Published Online 1 November 2004mentioning
confidence: 96%
“…Recent genomic analyses of a variety of human cancers found that somatic mutations in ATM are relatively common and appear to be a driving force in tumorigenesis (Davies et al, 2005;Greenman et al, 2007). Silencing of ATM gene expression by promoter hypermethylation has also been shown to frequently occur in several human cancers (Ai et al, 2004;Vo et al, 2004;Safar et al, 2005). Kinzler and Vogelstein (Kinzler and Vogelstein, 1997) originally classified tumor suppressors into two main categories: gatekeepers and caretakers.…”
Section: Discussionmentioning
confidence: 99%
“…Since methylation of a tumor suppressor gene does not mean that each CpG site is methylated and that methylation is 100% at each site, primer design has a big impact on the results. 44 However, the ATM gene is a target for epigenetic silencing in advanced breast cancer, 45 head and neck cancer 46 and colorectal cancer. 47 Future studies will have to clarify whether promoter methylation, which was shown in four of the five cell lines for the first time, induces relevant inactivation of ATM in patients with MCL and CLL and whether it is associated with the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%